Motivation, Induction and Challenge: Examining the Initial Phase of International Students' Educational Sojourn - Cowley, Paul; Hyams–Ssekasi, Denis (Journal of International Students, 2018)
This study explores the initial higher education experiences of first-year international students in the UK. Questionnaires and semi-structured interviews were carried out with 20 new international students undertaking a business degree at a UK university. The students described the key motivating factors for studying abroad and the fundamental issues and challenges they encountered. The language barrier, academic skills and orientation were highlighted as being integral to their development. A comprehension of international students’ initial academic and social needs is important in enabling universities to develop systems that will meet the prevailing needs of these learners.